The characterization and properties of recycled natural latex gloves (rNL-G) filled acrylonitrile butadiene rubber (NBR) compounds - Dahham, Omar Sabbar (School of Material Engineering, 2015)
The major aim of this research is to study the possibility of producing a new elastomeric material with acceptable properties from compounding the recycled natural latex gloves (rNL-G) with virgin acrylonitrile butadiene rubber (NBR). Therefore it can be pouline as follows to investigate the effects of different sizes of recycled natural latex gloves (rNL-G) on properties of NBR/rNL-G compounds; to study the effects of sawdust short fiber (SD) as natural filler on properties of NBR/rNL-G/SD compounds; to determine the effects of trans-polyoctylene rubber (TOR) as a compatibilizer on properties of NBR/rNL-G/TOR compounds.